The Effect of Implementation of Good Corporate Governance And Sharia Compliance On Customer Satisfaction of Bank Syariah Indonesia Sub-Branch Office Medan Cemara Asri - Sinaga, Muhammad Syahputra; Nasution, Muhammad Lathief Ilhamy; Anggraini, Tuti (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2024)
Both commercial banks and Islamic banks, good corporate governance (Gcg) and sharia compliance (SC) are fundamental elements. The effect of sharia compliance and good corporate governance on customer satisfaction and loyalty at Bank Syariah Indonesia Medan KC Cemara Asri, after processing and statistical analysis of the data obtained from the questionnaire answers in the IBM SPSS Statistics 25 program is at Bank Syariah Indonesia Sub-Branch Medan Cemara Asri, good corporate governance has a positive and significant effect on customer loyalty is one of the positive and large effects of good corporate governance features at Bank Syariah Indonesia Sub-Branch Medan Cemara Asri, Medan. At Bank Syariah Indonesia Sub-Branch Medan Cemara Asri, customer satisfaction is positively influenced by the Sharia Compliance variable. In accordance with the name of the institution, Bank Syariah Indonesia Sub-Branch Medan Cemara Asri has carried out sharia compliance well. The customer loyalty variable is positively and significantly influenced by the sharia compliance variable. The stronger the foundation, the more customers will trust the bank to be involved in their transactions. These elements are the basis for assessing the satisfaction of bank customers in using bank services during transactions. The questionnaire is one of the techniques or procedures that researchers can use to collect data in this study. Validity test, reliability test, normality test, classical assumption test, multiple linear regression test, hypothesis test, and coefficient of determination test are procedures used for data analysis. In this study, quantitative research was used.